Diversity studies in the interaction between the anthracnose fungus Colletotrichum gloeosporioides and its host plant Stylosanthes spp. in Mexico - Gama-López, S.; Munaut, F.; Vander Stappen, J.; Scheldeman, K.; Damme, V. van (2007)
Pests and diseases are important constraints to production in both traditional and modern agricultural systems. It is widely accepted that crop diversity, mainly through use of resistance and tolerance genes, is an important asset in reducing the risk of crop losses related to pests and diseases. However, little is known about the effect of the natural pathogen diversity on the occurrence and severity of phytopathological infestations. This publication summarizes the results of the multidisciplinary project ‘Genetic diversity studies in the interaction between the anthracnose fungus Colletotrichum gloeosporioides and its host plant Stylosanthes spp.’ The legume Stylosanthes is an important forage crop worldwide and Colletotrichum gloeosporioides is its most important pathogen. This project was a multidisciplinary bi-national effort centred in Mexico, a centre of origin of the host plant, which focused on characterizing both the host plant and the pathogen using different characterization techniques, from macro-morphological through molecular. As anthracnosis is reducing Stylosanthes yields from Africa to Australia, an increased knowledge and understanding of the co-existence of crop and pathogen diversity will benefit stakeholders outside the study area as well. A team of international researchers undertook a coordinated effort to increase the inclusion of information on host and pathogen diversity in areas where the crop and its pathogen are native. The Unité de Phytopathologie de l’Université catholique de Louvain, Louvain-la-Neuve, Belgium (UCL) focused on the characterization of C. gloeosporioides and other Colletotrichum species associated with wild Stylosanthes species in Mexico, while Stylosanthes diversity and taxonomy were studied by the Laboratorio de Recursos Naturales, Unidad de Biología, Tecnología y Prototipos, Facultad de Estudios Superiores Iztacala de la Universidad Nacional Autónoma de México (UNAM) at the morphological level and by the Laboratory of Gene Technology, Katholieke Universiteit Leuven, Belgium (KUL) that studied the material at the molecular level. The Mexican partner, UNAM, was responsible for the collection of materials, both host plant and pathogen, while the Belgian partners, UCL and KUL, carried out the molecular analysis. This study is a clear example of how a collaborative, multidisciplinary effort, including the exchange of plant material, allows for the optimal use of existing synergies between different research centres, leading to a better understanding of a complex theme such as host-pathogen diversity. This will permit a better use of the crop’s genetic diversity, and the corresponding resistance genes available, as well as the application of better screening methods for pest or disease resistance, based on a more extensive pathogen diversity. Bioversity International, formerly known as IPGRI, and its Regional Office for the Americas in Cali, Colombia is honoured that it was allowed to coordinate this project.